A rare complication after septoplasty procedure in a misdiagnosed submucous cleft palate case: Palatal fistula - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
Nasal septoplasty is a common and low-risk procedure performed very frequently in plastic surgery as well as in otorhinolaryngology. The development of a palatal perforation following a nasal septoplasty procedure is a very rare event with only a few cases reported in the literature. A patient with palatal fistula formation after septoplasty procedure is presented here, who was later on diagnosed with submucous cleft palate during the repair of the palatal fistula. (C) 2010 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Palatal fistula; Septoplasty; Submucous cleft palate